Diseño de un museo virtual de la cerámica perteneciente a la cultura panzaleo, a través de herramientas multimedias y 3d, el cual servirá como medio de difusión y preservación cultural, durante el período 2013 - Mogollón Naranjo, Yeseña Rosalía (2015)
This research topic makes possible to spread and preserve Panzaleo culture through technological means to strengthen teaching and learning systems, in order to provide interactive and fast information in a timely. For the development of this proposal was sampled Machachi Educative Unit, the data obtained from the applied surveys show that 51.05% of surveyed students have not knowledge about a virtual museum and 51.58% of them do not know Panzaleo culture, also they do not have a didactic resource that show them information about Panzaleo culture, It arises to design a virtual museum in order to make it useful for students and for all kind of people in order to provide basic information about Panzaleo culture to link young people with cultural identity of indigenous towns....